Overview of Routine Hematology Results in COVID-19 Patients at UKRIDA Hospital in 2021 - Sinsanta Sinsanta; Inneke Kusumawati Susanto; Chandra Priawan (Jurnal MedScientiae, 2023)
Coronavirus Disease 2019, more commonly known as COVID-19, is an infectious disease that has a contagious nature, the etiologic cause is Severe Acute Respiratory Syndrome Coronavirus 2. Several clinical manifestations that commonly occur when infected with COVID-19 include acute respiratory system disorders, for example cough, fever and shortness of breath. on March 12 2020, WHO confirmed that COVID-19 was a pandemic case. This research was conducted in a cross-sectional descriptive manner, using consecutive sampling with a total sample of 110 patients, using secondary data in the form of medical records. It was concluded that the results of routine hematological examinations (hemoglobin, hematocrit, erythrocytes, leukocytes, platelets) were mostly normal, this was because the patients in the study sample were patients who had recently been infected with the Covid-19 virus, and the medical records taken were the results of a hematological examination. the first time when I entered the hospital. On examination of hemoglobin found 22 patients (20%) decreased. On leukocyte examination, it was found that 28 patients (25.5%) experienced a decrease in platelets, 15 patients (13.6%) decreased.